The Subantarctic Rayadito (Aphrastura subantarctica), a new bird species on the southernmost islands of the Americas - Rozzi, Ricardo (2022)
We describe a new taxon of terrestrial bird of the genus Aphrastura (rayaditos) inhabiting the Diego Ramírez Archipelago, the southernmost point of the American continent. This archipelago is geographically isolated and lacks terrestrial mammalian predators as well as woody plants, providing a contrasted habitat to the forests inhabited by the other two Aphrastura spp. Individuals of Diego Ramírez differ morphologically from Aphrastura spinicauda, the taxonomic group they were originally attributed to, by their larger beaks, longer tarsi, shorter tails, and larger body mass. These birds move at shorter distances from ground level, and instead of nesting in cavities in trees, they breed in cavities in the ground, reflecting different life-histories. Both taxa are genetically differentiated based on mitochondrial and autosomal markers, with no evidence of current gene flow. Although further research is required to define how far divergence has proceeded along the speciation continuum, we propose A. subantarctica as a new taxonomic unit, given its unique morphological, genetic, and behavioral attributes in a non-forested habitat. The discovery of this endemic passerine highlights the need to monitor and conserve this still-pristine archipelago devoid of exotic species, which is now protected by the recently created Diego Ramírez Islands-Drake Passage Marine Park.